Solid electrolytic capacitor
By using conductive polymers in solid electrolytic capacitors and controlling their weight, combined with liquid components, the problem of difficulty in achieving high voltage withstand voltage in the prior art is solved, and the effect of taking into account low ESR and high voltage withstand voltage is achieved.
Patent Information
- Application Number
- CN202380066174.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-29
- Filing Date
- 2023-08-14
- Publication Date
- 2025-04-22
AI Technical Summary
While maintaining low equivalent series resistance (ESR), existing solid electrolytic capacitors have difficulty achieving high voltage withstand voltage, especially in the field of power electronics technology.
By using a conductive polymer as the solid electrolyte layer in a solid electrolyte capacitor, and controlling the weight of the conductive polymer to be less than 11 mg/cm3, the possible liquid components are combined to optimize the performance of the capacitor.
It realizes the effect of solid electrolytic capacitors that have both low ESR and high withstand voltage, meeting the demand for high withstand voltage in power electronic technology and other fields.
Smart Images

Figure CN119866531A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid electrolytic capacitor in which the electrolyte is a solid electrolyte layer or a solid electrolyte layer and a liquid component. Background Art
[0002] Electrolytic capacitors include valve metals such as tantalum or aluminum as anode foil and cathode foil. The anode foil is expanded by forming the valve metal into a sintered body or an etched foil, and the expanded surface is treated by anodization to have a dielectric film. An electrolyte is present between the anode foil and the cathode foil.
[0003] The electrolytic capacitor can increase the specific surface area by expanding the anode foil, and has the advantage of easily obtaining a large electrostatic capacitance compared to other types of capacitors. In addition, the electrolytic capacitor includes an electrolyte in the form of an electrolyte. The contact area between the electrolyte and the dielectric film of the anode foil increases. Therefore, the electrostatic capacitance of the electrolytic capacitor is more likely to increase. However, the electrolyte evaporates and dissipates to the outside over time, and the electrolytic capacitor causes a decrease in electrostatic capacitance or an increase in dielectric loss tangent over time, thereby ushering in drying.
[0004] Therefore, among electrolytic capacitors, solid electrolytic capacitors using solid electrolytes have attracted much attention. As solid electrolytes, manganese dioxide or 7,7,8,8-tetracyanoquinodimethane (TCNQ) complexes are known. In recent years, conductive polymers derived from monomers having π conjugated double bonds, such as poly(3,4-ethylenedioxythiophene) (PEDOT), which have a slow reaction rate and excellent adhesion to the dielectric film, have rapidly become popular as solid electrolytes. Conductive polymers use acid compounds such as polyanions as dopants, or have partial structures in the monomer molecules that act as dopants, and exhibit high conductivity. Therefore, solid electrolytic capacitors have the advantage of lowering the equivalent series resistance (ESR).
[0005] Compared with liquid-type electrolytic capacitors in which the electrolyte is impregnated in the capacitor element, solid electrolytic capacitors lack the ability to repair defects in the anodic oxide film as a dielectric, and there is a risk of increased leakage current. Therefore, a so-called hybrid solid electrolytic capacitor has been proposed, in which a solid electrolyte layer is formed in the capacitor element where the anode foil and the cathode foil face each other with a partition in the middle, and a driving electrolyte is impregnated in the gap of the capacitor element.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2008-109068
[0009] Patent Document 2: Japanese Patent No. 4536625 Summary of the invention
[0010] Problems to be solved by the invention
[0011] Capacitors are used in various applications. For example, in the field of power electronics, in a power supply circuit that converts the power of an AC power source into DC power using a converter circuit and converts the DC power into the desired AC power using an inverter circuit, a smoothing capacitor is provided to suppress and smooth the DC ripple output from the converter circuit before inputting it into the inverter circuit. In addition, a decoupling capacitor is provided near a semiconductor switching element such as gallium nitride for stable operation or noise removal.
[0012] With the recent increase in power consumption, higher withstand voltage is required for solid electrolytic capacitors. For example, depending on the field of power electronics technology, capacitors with a withstand voltage of at least 200V can be expected. However, it is not easy to achieve a high withstand voltage while maintaining the low ESR that is an advantage of solid electrolytic capacitors.
[0013] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a solid electrolytic capacitor having both low ESR and high withstand voltage.
[0014] Technical means of solving problems
[0015] In order to solve the above-mentioned problem, a solid electrolytic capacitor of the present embodiment includes a capacitor element having an anode foil, a cathode body, and an electrolyte, wherein the anode foil has a surface expanded by a tunnel-shaped etching pit and has a dielectric film on the surface, the cathode body faces the anode foil, and the electrolyte includes a solid electrolyte layer containing a conductive polymer, wherein the weight of the conductive polymer is 11 mg / cm per unit volume of the capacitor element. 3 the following.
[0016] The weight of the conductive polymer per unit volume of the capacitor element may be 2 mg / cm 3 Above and 11mg / cm 3 the following.
[0017] The weight of the conductive polymer per unit volume of the capacitor element may be 6.2 mg / cm 3 Above and 9.0mg / cm 3 the following.
[0018] A liquid component filled in the gaps of the capacitor element may be included.
[0019] The conductive polymer may be contained in a conductive polymer liquid in which the conductive polymer is dispersed or dissolved, and part or all of the solvent.
[0020] The solid electrolyte layer may include a compound having a hydroxyl group.
[0021] Effects of the Invention
[0022] According to the present invention, a solid electrolytic capacitor has both low ESR and high withstand voltage. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] [ Figure 1 ] is a graph showing the relationship between the weight of the conductive polymer and the withstand voltage of Examples 1 to 8, and the relationship between the weight of the conductive polymer and the ESR.
[0024] [ Figure 2 ] is a graph showing the relationship between the weight of the conductive polymer and the withstand voltage, and the relationship between the weight of the conductive polymer and the ESR of Examples 9 to 17. DETAILED DESCRIPTION
[0025] (Solid Electrolytic Capacitors)
[0026] A solid electrolytic capacitor has a pair of electrode bodies and an electrolyte layer. One of the electrode bodies is an anode foil, and a dielectric film is formed on the foil surface. The other electrode body is a cathode body. The cathode body and the anode foil are arranged facing each other. The pair of electrode bodies are arranged facing each other with the electrolyte layer sandwiched between them. The assembly formed by combining the pair of electrode bodies and the electrolyte layer is called a capacitor element.
[0027] The capacitor element sometimes includes a separator. The separator is interposed between a pair of electrode bodies, thereby isolating the anode foil from the cathode body, preventing short circuits, and maintaining the electrolyte layer. In the case where the shape of the electrolyte layer can be maintained by itself and the pair of electrode bodies can be isolated by the electrolyte layer, the separator can be omitted from the capacitor element.
[0028] The anode lead is connected to the anode foil, and the cathode lead is connected to the cathode body. The solid electrolytic capacitor is electrically connected to the mounting circuit via the anode lead and the cathode lead. By being connected to the mounting circuit, the solid electrolytic capacitor becomes a passive element that obtains electrostatic capacitance through the dielectric polarization of the dielectric film and performs charge storage and discharge.
[0029] (Electrode body)
[0030] In this type of solid electrolytic capacitor, the electrode body is a foil body made of valve metal. In the wound type, a long strip shape made by extending the valve metal is mostly used, and in the flat plate type, a flat plate made by extending the valve metal is mostly used. Valve metals include aluminum, tantalum, niobium, niobium oxide, titanium, hafnium, zirconium, zinc, tungsten, bismuth and antimony. Regarding purity, the anode foil is ideally 99.9% or more, and the cathode body is ideally 99% or more, and may also contain impurities such as silicon, iron, copper, magnesium, and zinc.
[0031] An expansion layer is formed on one or both sides of the anode foil. The expansion layer is an etching layer having a plurality of tunnel-shaped etching pits. The tunnel-shaped etching pits are holes dug in the thickness direction of the foil. The tunnel-shaped pits may penetrate the foil or may be a length where the deepest part stays in the foil. The tunnel-shaped etching pits are typically formed by passing a direct current through an acidic aqueous solution such as hydrochloric acid in which halogen ions exist. The tunnel-shaped etching pits are further expanded by passing a direct current through an acidic aqueous solution such as nitric acid.
[0032] As the cathode body, for example, a foil-shaped cathode foil can also be used. In addition, the cathode body can also be a laminate of a metal layer such as silver and a carbon layer. A surface expansion layer can also be formed on one side or both sides of the cathode foil. A flat foil without a surface expansion layer can also be used as the cathode foil. The surface expansion layer of the cathode foil is an etching layer, a sintered layer formed by sintering valve metal powder, or a vapor-deposited layer formed by vapor-depositing valve metal particles on the foil. That is, the surface expansion layer of the cathode foil contains tunnel-shaped pits, sponge-shaped pits, or dense powders or gaps between particles.
[0033] The dielectric film is formed on the concavo-convex surface of the expansion layer. The dielectric film is typically an oxide film formed on the surface layer of the anode foil. If the anode foil is an aluminum foil, it is an aluminum oxide layer that oxidizes the surface of the expansion layer. In the chemical conversion treatment for forming the dielectric film, a voltage is applied to the anode foil in a chemical conversion solution with the desired withstand voltage as the target. The chemical conversion solution is a solution without halogen ions, for example, a phosphoric acid-based chemical conversion solution such as ammonium dihydrogen phosphate, a boric acid-based chemical conversion solution such as ammonium borate, and an adipic acid-based chemical conversion solution such as ammonium adipate.
[0034] The cathode body may have a natural oxide film or a thin oxide film (about 1 V to 10 V) formed by chemical conversion treatment. The natural oxide film is formed by the reaction of the cathode body with oxygen in the air.
[0035] (Electrolyte layer)
[0036] The electrolyte layer is attached to at least a portion of the dielectric membrane of the anode foil, becoming the true cathode of the solid electrolytic capacitor. Preferably, the electrolyte layer is in close contact with the entire area of the dielectric membrane and is connected to the surface of the cathode body. The electrolyte layer is a solid electrolyte layer, or includes a solid electrolyte layer and a liquid component. The solid electrolyte layer contains a conductive polymer. The liquid component is a driving electrolyte or a solvent portion of the electrolyte impregnated in the gap of the capacitor element formed with the solid electrolyte layer.
[0037] (Solid electrolyte layer)
[0038] Conductive polymers are self-doped polymers doped with dopant molecules within the molecule or conjugated polymers doped with external dopant molecules. Conjugated polymers are obtained by chemical oxidation polymerization or electrolytic oxidation polymerization of monomers or derivatives having π conjugated double bonds. Doped conjugated polymers exhibit high conductivity. That is, conductivity is exhibited by adding a small amount of dopants such as acceptors that easily accept electrons or donors that easily donate electrons to conjugated polymers.
[0039] The solid electrolyte layer is formed using a conductive polymer liquid. The conductive polymer liquid is a liquid in which particles or powders of a conductive polymer are dispersed or dissolved. Additives are added to the conductive polymer liquid as needed. At least an anode foil, a pair of electrode bodies, a separator, or a capacitor element are immersed in the conductive polymer liquid, and then dried after immersion. In addition to immersion, the conductive polymer liquid can also be applied by dropwise coating or spray coating. Thus, the conductive polymer and the additive are attached to form a solid electrolyte layer. The solid electrolyte layer may also contain part or all of the solvent that has not volatilized from the conductive polymer liquid.
[0040] The weight of the conductive polymer contained in the solid electrolyte layer per unit volume of the capacitor element is 11 mg / cm 3 If the concentration per unit volume of the capacitor element is 11 mg / cm 3 In addition, the weight of the conductive polymer is preferably 2 mg / cm2 per unit volume of the capacitor element. 3 If 2mg / cm 3 Above and 11mg / cm 3 In the following range, the ESR is particularly low.
[0041] In particular, the weight of the conductive polymer per unit volume of the capacitor element is preferably 6.2 mg / cm 3 Above 9mg / cm 3If the weight of the conductive polymer is within the above range, the ESR becomes particularly low and minimized, and the withstand voltage becomes particularly high and maximized. If it deviates from the above range, although the absolute values are low ESR and high withstand voltage, the ESR increases compared to the above range, and the withstand voltage decreases compared to the above range.
[0042] Regarding the weight adjustment of the conductive polymer in the solid electrolyte layer, it is only necessary to adjust the amount of the conductive polymer dispersed or dissolved in the conductive polymer liquid, or the amount of the dispersion medium or solvent. Regarding the weight of the conductive polymer actually contained in the solid electrolyte layer, first, the weight of the capacitor element is measured before and after the solid electrolyte layer is formed and the difference is calculated. Then, it is only necessary to calculate the weight of the conductive polymer contained in the solid electrolyte layer based on the differential value and the concentration of the conductive polymer contained in the conductive polymer liquid. In addition, the solid electrolytic capacitor can also be decomposed to extract only the conductive polymer.
[0043] In such a solid electrolyte layer, as a conjugated polymer, known polymers can be used without particular limitation. For example, polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, polyphenylene, polyphenylenevinylene, polyacene, polythiophenevinylene, etc. can be mentioned. These conjugated polymers can be used alone, or two or more can be combined, and further can be a copolymer of two or more monomers.
[0044] Among the conjugated polymers, a conjugated polymer obtained by polymerizing thiophene or its derivatives is preferred, and a conjugated polymer obtained by polymerizing 3,4-ethylenedioxythiophene (i.e., 2,3-dihydrothieno[3,4-b][1,4]dioxin), 3-alkylthiophene, 3-alkoxythiophene, 3-alkyl-4-alkoxythiophene, 3,4-alkylthiophene, 3,4-alkoxythiophene, or derivatives thereof is preferred. As a thiophene derivative, a compound selected from thiophenes having substituents at the 3- and 4-positions is preferred, and the substituents at the 3- and 4-positions of the thiophene ring can form a ring together with the carbons at the 3- and 4-positions. The number of carbon atoms in the alkyl or alkoxy group is preferably 1 to 16.
[0045] In particular, a polymer of 3,4-ethylenedioxythiophene called EDOT, that is, poly(3,4-ethylenedioxythiophene) called PEDOT is particularly preferred. In addition, a substituent may be added to 3,4-ethylenedioxythiophene. For example, an alkylated ethylenedioxythiophene to which an alkyl group having 1 to 5 carbon atoms is added as a substituent may be used. Examples of the alkylated ethylenedioxythiophene include methylated ethylenedioxythiophene (i.e., 2-methyl-2,3-dihydro-thieno〔3,4-b〕〔1,4〕dioxin), ethylated ethylenedioxythiophene (i.e., 2-ethyl-2,3-dihydro-thieno〔3,4-b〕〔1,4〕dioxin), butylated ethylenedioxythiophene (i.e., 2-butyl-2,3-dihydro-thieno〔3,4-b〕〔1,4〕dioxin), and 2-alkyl-3,4-ethylenedioxythiophene.
[0046] The dopant may be a known one without particular limitation. The dopant may be used alone or in combination of two or more. In addition, a polymer or a monomer may be used. For example, as a dopant, inorganic acids such as polyanions, boric acid, nitric acid, and phosphoric acid; organic acids such as acetic acid, oxalic acid, citric acid, tartaric acid, squaric acid, rhodizonic acid, croconic acid, salicylic acid, p-toluenesulfonic acid, 1,2-dihydroxy-3,5-benzenedisulfonic acid, methanesulfonic acid, trifluoromethanesulfonic acid, borodisalicylic acid, bisoxalylboric acid, sulfonylimide acid, dodecylbenzenesulfonic acid, propylnaphthalenesulfonic acid, and butylnaphthalenesulfonic acid may be cited.
[0047] The polyanion is, for example, a substituted or unsubstituted polyalkylene, a substituted or unsubstituted polyalkenylene, a substituted or unsubstituted polyimide, a substituted or unsubstituted polyamide, or a substituted or unsubstituted polyester, and examples thereof include a polymer containing only a structural unit having an anionic group, and a polymer containing a structural unit having an anionic group and a structural unit not having an anionic group. Specifically, examples of the polyanion include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacrylic acid sulfonic acid, polymethacrylic acid sulfonic acid, poly(2-acrylamide-2-methylpropanesulfonic acid), polyisoprene sulfonic acid, polyacrylic acid, polymethacrylic acid, and polymaleic acid.
[0048] The solvent of the conductive polymer liquid, i.e., the residual solvent in the solid electrolyte layer, can be used as long as it disperses or dissolves the conductive polymer, and is preferably water or a mixture of water and an organic solvent. Examples of the organic solvent include polar solvents, alcohols, esters, hydrocarbons, carbonate compounds, ether compounds, chain ethers, heterocyclic compounds, nitrile compounds, etc.
[0049] As polar solvents, N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, etc. can be listed. As alcohols, methanol, ethanol, propanol, butanol, etc. can be listed. As esters, ethyl acetate, propyl acetate, butyl acetate, etc. can be listed. As hydrocarbons, hexane, heptane, benzene, toluene, xylene, etc. can be listed. As carbonate compounds, ethylene carbonate, propylene carbonate, etc. can be listed. As ether compounds, dioxane, diethyl ether, etc. can be listed. As chain ethers, ethylene glycol dialkyl ethers, propylene glycol dialkyl ethers, polyethylene glycol dialkyl ethers, polypropylene glycol dialkyl ethers, etc. can be listed. As heterocyclic compounds, 3-methyl-2-oxazolidinone, etc. can be listed. As nitrile compounds, acetonitrile, glutaronitrile, methoxyacetonitrile, propionitrile, benzonitrile, etc. can be listed.
[0050] Examples of additives to the conductive polymer liquid include polyols, organic binders, surfactants, dispersants, defoamers, coupling agents, antioxidants, ultraviolet absorbers, etc. Examples of polyols include sorbitol, ethylene glycol, propylene glycol, butylene glycol, pentanediol, hexanediol, heptanediol, octanediol, diethylene glycol, triethylene glycol, polyoxyalkylene glycol, glycerol, polyglycerol, polyoxyalkylene glycerol, xylitol, erythritol, mannitol, dipentaerythritol, pentaerythritol, sulfolane, methyl sulfolane, or a combination of two or more thereof.
[0051] As a solvent, additive or both constituting such a conductive polymer liquid, a compound having a hydrophilic group or a hydrophilic molecule such as a hydroxyl group is preferred. As a compound having a hydroxyl group, for example, polyols such as ethylene glycol and glycerol can be cited. By using a compound having a hydroxyl group, a change in the higher-order structure of the conductive polymer can be caused, and the ESR reduction or withstand voltage improvement effect of the solid electrolytic capacitor can be obtained. In addition, the boiling point of the polyol is high, and it remains in the electrolyte layer, and it is easy to form a solid electrolyte layer.
[0052] (liquid ingredient)
[0053] The liquid component is a driving electrolyte or a solvent portion of the driving electrolyte. Examples of the solvent of the driving electrolyte include protic organic polar solvents and aprotic organic polar solvents, which may be used alone or in combination of two or more.
[0054] Examples of protic organic solvents as solvents include monohydric alcohols, polyhydric alcohols, and oxyhydric alcohol compounds. Examples of monohydric alcohols include ethanol, propanol, butanol, pentanol, hexanol, cyclobutanol, cyclopentanol, cyclohexanol, and benzyl alcohol. Examples of polyhydric alcohols and oxyhydric alcohol compounds include ethylene glycol, diethylene glycol, propylene glycol, glycerol, methyl cellosolve, ethyl cellosolve, methoxypropylene glycol, dimethoxypropanol, polyglycerol, polyethylene glycol, polyoxyethylene glycerol, and alkylene oxide adducts of polyhydric alcohols such as polypropylene glycol.
[0055] As a non-protonic organic polar solvent of the solvent, sulfone series, amide series, lactone series, cyclic amide series, nitrile series, sulfoxide series, etc. can be listed as representatives. As sulfone series, dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, cyclopentane, 3-methylcyclopentane, 2,4-dimethylcyclopentane, etc. can be listed. As amide series, N-methylformamide, N,N-dimethylformamide, N-ethylformamide, N,N-diethylformamide, N-methylacetamide, N,N-dimethylacetamide, N-ethylacetamide, N,N-diethylacetamide, etc. can be listed. As lactone series and cyclic amide series, γ-butyrolactone, γ-valerolactone, δ-valerolactone, N-methyl-2-pyrrolidone, ethylene carbonate, propylene carbonate, butylene carbonate, isobutylene carbonate, etc. can be listed. As nitrile series, acetonitrile, 3-methoxypropionitrile, glutaronitrile, etc. can be listed. Examples of the sulfoxide-based compounds include dimethyl sulfoxide and the like.
[0056] When the solute of the driving electrolyte is added to the liquid component, the solute is an anion component and a cationic component. The solute is typically a salt of an organic acid, a salt of an inorganic acid, or a salt of a composite compound of an organic acid and an inorganic acid, and can be used alone or in combination of two or more. The acid as an anion and the base as a cation can also be added to the solvent separately.
[0057] Examples of organic acids that serve as anion components as solutes include carboxylic acids such as oxalic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, adipic acid, benzoic acid, toluic acid, heptanoic acid, malonic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, azelaic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, tridecanedicarboxylic acid, tert-butyladipic acid, 11-vinyl-8-octadecenedicarboxylic acid, resorcinolic acid, pyrogallolic acid, gallic acid, gentisic acid, protocatechuic acid, catecholcarboxylic acid, trimellitic acid, and pyromellitic acid, or phenols and sulfonic acids.
[0058] Inorganic acids include boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, carbonic acid, and silicic acid. Composite compounds of organic acids and inorganic acids include boron disalicylic acid, boron dioxalic acid, boron diglycolic acid, boron dimalonic acid, boron disuccinic acid, boron diadipic acid, boron diazelaic acid, boron dibenzoic acid, boron dimaleic acid, boron dilactic acid, boron dimalic acid, boron ditartaric acid, boron dicitric acid, boron diphthalic acid, boron di(2-hydroxy)isobutyric acid, boron diresorcinolic acid, boron dimethylsalicylic acid, boron dinaphthoic acid, boron dimandelic acid, and boron di(3-hydroxy)propionic acid.
[0059] In addition, as at least one salt of an organic acid, an inorganic acid, and a composite compound of an organic acid and an inorganic acid, for example, ammonium salts, quaternary ammonium salts, quaternary amidinium salts, amine salts, sodium salts, potassium salts, etc. Examples of quaternary ammonium ions of quaternary ammonium salts include tetramethylammonium, triethylmethylammonium, tetraethylammonium, etc. Examples of quaternary amidinium include ethyldimethylimidazolinium, tetramethylimidazolinium, etc. Examples of amine salts include salts of primary amines, secondary amines, and tertiary amines. Examples of primary amines include methylamine, ethylamine, propylamine, etc. Examples of secondary amines include dimethylamine, diethylamine, ethylmethylamine, dibutylamine, etc. Examples of tertiary amines include trimethylamine, triethylamine, tributylamine, ethyldimethylamine, ethyldiisopropylamine, etc.
[0060] Furthermore, other additives may be added to the electrolyte. Examples of additives include alkylene oxide adducts of polyols such as polyethylene glycol or polyoxyethylene glycerol, complex compounds of boric acid and polysaccharides (mannitol, sorbitol, etc.), complex compounds of boric acid and polyols, boric acid esters, nitro compounds (o-nitrobenzoic acid, m-nitrobenzoic acid, p-nitrobenzoic acid, o-nitrophenol, m-nitrophenol, p-nitrophenol, p-nitrobenzyl alcohol, etc.), phosphates, etc. These may be used alone or in combination of two or more.
[0061] (Partition)
[0062] Examples of the separator include cellulose such as kraft paper, Manila hemp, esparto, hemp, rayon, and mixed papers thereof, polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof, polytetrafluoroethylene resins, polyvinylidene fluoride resins, vinylon resins, aliphatic polyamides, semi-aromatic polyamides, wholly aromatic polyamides, and other polyamide resins, polyimide resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, polyvinyl alcohol resins, and the like. These resins can be used alone or in combination.
[0063] [Example]
[0064] Hereinafter, the present invention will be described in more detail based on examples. In addition, the present invention is not limited to the following examples.
[0065] (Example 1-Example 8)
[0066] The solid electrolytic capacitors of Examples 1 to 8 were prepared as follows. The solid electrolytic capacitors of Examples 1 to 8 were non-hybrid type, and the electrolyte layer did not contain a liquid component.
[0067] First, the two electrode bodies are set as long strip-shaped aluminum foil. Tunnel-shaped pits are formed on both sides of the anode foil by DC etching. In addition, a dielectric film is formed on the anode foil by chemical conversion treatment. In the chemical conversion treatment, the applied voltage is made to reach 650V. As for the cathode foil, pits are formed on both sides by AC etching, and an oxide film is formed by chemical conversion treatment with a chemical conversion voltage of 3Vfs. Leads are connected to the two electrode bodies, and the two electrode bodies are wound facing each other through a separator made of Manila hemp. Then, the repair chemical conversion is carried out by an aqueous ammonium borate solution.
[0068] Next, after the capacitor element is immersed in the conductive polymer liquid and the conductive polymer liquid is impregnated in the capacitor element, the capacitor element is dried at 110° C. Polyethylene dioxythiophene (PEDOT / polystyrene sulfonic acid (PSS)) doped with polystyrene sulfonic acid as a conductive polymer is dispersed in the conductive polymer liquid. The solvent of the conductive polymer liquid is a mixed liquid of 90wt% water and 10wt% ethylene glycol.
[0069] Thus, a solid electrolyte layer is formed in the capacitor element. Here, the weight of the conductive polymer in the solid electrolyte layer of Examples 1 to 8 is different. The weight of the conductive polymer is the weight per unit volume of the capacitor element, hereinafter referred to as the conductive polymer weight. The conductive polymer weight is adjusted by the concentration of PEDOT / PSS dispersed or dissolved in the conductive polymer liquid.
[0070] Thus, the solid electrolytic capacitors of Examples 1 to 8 were manufactured with the same structure, composition, manufacturing method and manufacturing conditions except for the weight of the conductive polymer.
[0071] (Withstand voltage and ESR)
[0072] The withstand voltage of the solid electrolytic capacitors of Examples 1 to 8 was measured. The withstand voltage was measured as follows. That is, a voltage was applied to the solid electrolytic capacitor at 105°C. The starting voltage was 200V, and the applied voltage was increased by 1V every 10 seconds. Then, the voltage when the current flowing into the solid electrolytic capacitor reached 1mA was taken as the withstand voltage.
[0073] In addition, the ESR of the solid electrolytic capacitors of Examples 1 to 8 was measured. The method for measuring the withstand voltage is as follows. The ESR was measured at room temperature using an LCR meter manufactured by NF CORPORATION Co., Ltd. The measurement frequency was 100 kHz and the AC amplitude was a sine wave of 0.5 Vms.
[0074] The measurement results of the withstand voltage and ESR are shown in the following Table 1 together with the weight of the conductive polymer of Examples 1 to 8. In Table 1, the weight of the conductive polymer is expressed as the molecular weight of the conductive polymer per unit volume of the element.
[0075] (Table 1)
[0076]
[0077] As shown in Table 1, the weight of the conductive polymer is converted to the weight per unit volume of the capacitor element (mg / cm 3 ), from 1.2 mg / cm 3 Up to 11.0mg / cm 3 The weight of each conductive polymer was calculated by subtracting the weight of the capacitor element before immersion from the weight of the capacitor element after immersion in the conductive polymer solution and before drying, and multiplying the difference by the PEDOT / PSS concentration.
[0078] Based on Table 1, the relationship between the weight of the conductive polymer and the withstand voltage, and the relationship between the weight of the conductive polymer and the ESR are shown in Figure 1 in the chart. Figure 1 In the figure, the black plot is the withstand voltage, and the white plot is the ESR. In addition, the ESR is expressed in logarithms.
[0079] As shown in Table 1 and Figure 1 As shown in the figure, regarding the withstand voltage, if the weight of the conductive polymer is up to 11.0 mg / cm 3 In the whole range up to 9.0mg / cm, the withstand voltage exceeds 200V. 3 The withstand voltage is maintained at a high level of over 500V. 3 The ESR is good in the entire range, especially 2.0mg / cm 3 ESR with 1.2mg / cm 3 Compared with 6.2mg / cm 3 Up to 9.0mg / cm 3 , ESR is minimized, but at 10.3mg / cm 3 After that, although the absolute value is good, it is still different from 8.6 mg / cm 3 Up to 9.0mg / cm 3 Compared with the range, it has increased dramatically.
[0080] Thus, if the weight of the conductive polymer is 11 mg / cm 3If the weight of the conductive polymer is 2 mg / cm 3 Above and 11mg / cm 3 Below, non-hybrid solid electrolytic capacitors have both lower ESR and high withstand voltage. In addition, if the weight of the conductive polymer is 6.2mg / cm 3 Above and 9.0mg / cm 3 The following results show that both the maximum withstand voltage and the minimum ESR can be obtained.
[0081] (Example 9-Example 17)
[0082] Furthermore, solid electrolytic capacitors of Examples 9 to 17 are prepared. The solid electrolytic capacitors of Examples 9 to 17 are hybrid types, and the electrolyte layer includes a solid electrolyte layer and a liquid component. The liquid component is 59.4wt% of ethylene glycol, 39.6wt% of polyethylene glycol and 1wt% of ammonium azelaic acid. The average molecular weight of polyethylene glycol is 1000. The liquid component is impregnated in the capacitor element. Except for the weight of the conductive polymer, the other same structure, the same composition, the same manufacturing method and the same manufacturing conditions are the same as those of Examples 1 to 8.
[0083] (Withstand voltage and ESR)
[0084] The withstand voltage of the solid electrolytic capacitors of Examples 9 to 17 was measured. The method and conditions for measuring the withstand voltage and ESR were the same as those of Examples 1 to 8. The method for confirming the weight of each conductive polymer was also the same as those of Examples 1 to 8.
[0085] The measurement results of withstand voltage and ESR are shown in the following Table 2 together with the weight of the conductive polymer of Examples 9 to 17. In Table 2, the weight of the conductive polymer is expressed as the amount of the solid electrolyte per unit volume of the element.
[0086] (Table 2)
[0087]
[0088] As shown in Table 2, the weight of the conductive polymer is converted to the weight per unit volume of the capacitor element (mg / cm 3 ), from 1.2 mg / cm 3 Up to 11mg / cm 3 Based on Table 2, the relationship between the weight of the conductive polymer and the withstand voltage, and the relationship between the weight of the conductive polymer and the ESR are shown in Figure 2 in the chart. Figure 2In the figure, the black plot is the withstand voltage, and the white plot is the ESR. In addition, the ESR is expressed in logarithms.
[0089] As shown in Table 2 and Figure 2 As shown in the figure, regarding the withstand voltage, if the weight of the conductive polymer is up to 11.0 mg / cm 3 In the whole range up to 9.0mg / cm, the withstand voltage exceeds 200V. 3 The withstand voltage is maintained at a high level of over 500V. 3 The ESR is good in the entire range, especially 2.0mg / cm 3 ESR with 1.2mg / cm 3 Compared with 6.2mg / cm 3 Up to 9.0mg / cm 3 , ESR is minimized.
[0090] Thus, even if the solid electrolytic capacitor is a hybrid type, if the weight of the conductive polymer is 11 mg / cm 3 In addition, even in the case of a hybrid type, if the weight of the conductive polymer is 2 mg / cm 3 Above and 11mg / cm 3 Below, it also has lower ESR and high withstand voltage. If the weight of the conductive polymer is 6.2mg / cm 3 Above and 9.0mg / cm 3 The following results show that both the maximum withstand voltage and the minimum ESR can be obtained.
Claims
1. A solid electrolytic capacitor, characterized in that: A capacitor element comprising an anode foil, a cathode body and an electrolyte, The anode foil has a surface that is expanded by tunnel-shaped etching pits and has a dielectric film on the surface. The cathode body faces the anode foil, The electrolyte includes a solid electrolyte layer containing a conductive polymer, The weight of the conductive polymer per unit volume of the capacitor element is 11 mg / cm 3 the following.
2. The solid electrolytic capacitor according to claim 1, characterized in that: The weight of the conductive polymer per unit volume of the capacitor element is 2 mg / cm 3 Above and 11mg / cm 3 the following.
3. The solid electrolytic capacitor according to claim 1, characterized in that: The weight of the conductive polymer per unit volume of the capacitor element is 6.2 mg / cm 3 Above and 9.0mg / cm 3 the following.
4. The solid electrolytic capacitor according to any one of claims 1 to 3, characterized in that: A liquid component is included to fill the gaps in the capacitor element.
5. The solid electrolytic capacitor according to any one of claims 1 to 3, characterized in that: The solid electrolyte layer includes the conductive polymer in a conductive polymer liquid in which the conductive polymer is dispersed or dissolved, and part or all of a solvent.
6. The solid electrolytic capacitor according to claim 5, characterized in that: The solid electrolyte layer includes a compound having a hydroxyl group.
Citation Information
Patent Citations
capacitor
JP2008109068A